Stiffness of Muscles and Tendons of the Lower Limb of Professional and Semiprofessional Athletes Using Shear Wave Elastography. (28th July 2022) - Romer, Claudia; Czupajllo, Julia; Zessin, Enrico; Fischer, Thomas; Wolfarth, Bernd; Lerchbaumer, Markus H.
Abstract : Objective: Shear wave elastography (SWE) allows assessment of muscle and tendon stiffness and can be used to diagnose soft tissue pathologies such as tendinopathies. In sports medicine, SWE may have the potential to uncover structural changes early on before they lead to functional impairment. To systematically analyze possible differences in tendon and muscle stiffness of the lower limb between professional (PG) and semiprofessional female athletes (SG) using SWE and to compile reference values for developing preventive medicine approaches for professional athletes. Methods: Standardized SWE of both lower limb tendons and muscles (Achilles tendon [AT], soleus muscle insertion [SM], patellar tendon [PT], quadriceps tendon [QT], vastus medialis muscle [VM]) in the longitudinal plane was performed with the tendons in relaxed position in 24 healthy professional female athletes (PG) in comparison with 24 healthy semiprofessional female athletes (SG). Results: Median tendon and muscle stiffness was significantly higher in professional athletes (AT:PG, 11.12 m/s vs SG, 7.33 m/s, P < .001; SM: 1.77 m/s vs 1.14 m/s, P < .001; VM: 1.63 m/s vs 0.87 m/s, P < .001; QT: 3.31 m/s vs 2.61 m/s, P < .05). There was no significant difference in patellar tendon stiffness between PG and SG (PT: 2.57 m/s vs 3.21, P = .25). Conclusion: Professional female athletes have higher stiffness values than semiprofessional female athletes in lower limb muscles and tendons, except for the patellar tendon. Knowledge of such differences is necessary for diagnosing tendinopathy and injuries. Musculoskeletal SWE could offer great benefits in sports medicine as well as in rehabilitation and preventive medicine.